2015
DOI: 10.1007/s12035-015-9249-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sites of Neuroprotective Action of Dimebon (Latrepirdine)

Abstract: Dimebon (latrepirdine) is an anti-histaminergic agent which belongs to a fast-growing group of "old" medicines suggested to be of therapeutic utility for pathological conditions different from their original design ("repositioning"). Here, we overview the most recent studies on Dimebon directed to pathological processes in the brain-involving in vivo models of proteinopathies. In the latter, neurodegenerative effects are attributed to a group of aggregate-prone proteins such as γ-synuclein, hyperphosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 57 publications
0
14
0
3
Order By: Relevance
“…Такое "репозиционирование" существующих лекарств представляется крайне привлекательным для инвестиций, поскольку оно сводит к минимуму риск неизвестных побочных эффектов, сокращает общее время клинических исследований, так как характеристики безопасности этих лекарств уже изучены ранее [205]. Интересно, что изучение случаев успешного применения известных препаратов для лечения нейродегенеративных заболеваний часто приводит к открытию новых фармакологических мишеней, как это произошло с препаратами Bexarotene и Dimebon [206].…”
Section: репозиционирование известных ранее лекарственных препаратовunclassified
“…Такое "репозиционирование" существующих лекарств представляется крайне привлекательным для инвестиций, поскольку оно сводит к минимуму риск неизвестных побочных эффектов, сокращает общее время клинических исследований, так как характеристики безопасности этих лекарств уже изучены ранее [205]. Интересно, что изучение случаев успешного применения известных препаратов для лечения нейродегенеративных заболеваний часто приводит к открытию новых фармакологических мишеней, как это произошло с препаратами Bexarotene и Dimebon [206].…”
Section: репозиционирование известных ранее лекарственных препаратовunclassified
“…Data from independent studies at several laboratories have demonstrated that compounds belonging to the gamma-carboline class are potential neuroprotective agents leading to reduced levels of pathogenic aggregation and/or activating the intracellular defense mechanisms of controlled degradation of aggregated proteins [7,8]. Initial findings for these gamma-carbolines properties were obtained in Dimebon studies showing a correction of the cognitive function in patients with Alzheimer's disease (AD), which is the most common neurodegenerative disease in the proteinopathy group [9,10].…”
Section: Neuroprotective Properties Of Gamma-carbolinesmentioning
confidence: 99%
“…However, the exact mechanism of Dimebon action remains unclear. The existing data from biochemical studies, as well as experiments on cell cultures and animals, suggest that Dimebon is a multitarget drug capable of affecting many intracellular processes and various pathogenic pathways in neurons and other cells affected by neurodegenerative changes [7].…”
Section: Effect Of Gamma-carbolines On the Progression Of Proteinopatmentioning
confidence: 99%
“…В качестве таких подходов можно отметить совмещение в одной структуре ингибиторных свойств холинэстеразы и моноаминоксидазы, антиоксидантных и металлохелатирующих свойств, способности выступать лигандами одновременно нескольких рецепторов, введение дополнительных NO-генерирующих фрагментов в базовую структуру лиганда. Примерами таких мультитаргетных агентов являются препарат лагостиджил [114] и отечественный препарат димебон, успешно прошедший 2-ю фазу клинических испытаний в России [115].…”
Section: рис 2 распределение препаратов по типу действия на различнunclassified